Gene repertoire of IGHV-IGHD-IGHJ rearrangements in Macedonian patients with chronic lymphocytic leukemia-single centre experience - Trajkova, Sanja (Medip Academy, 2016)
Background: B-cell chronic lymphocytic leukemia (CLL) is a clinically heterogeneous disease with many patients surviving for decades with watch and wait strategy or no treatment, whereas others surrender to their disease despite therapy. In recent years, new molecular prognostic factors came to light that have significantly improved the stratification of the CLL patients. One of the most important molecular predictors, the immunoglobulin VH gene mutational status, divides CLL into two prognostic groups, depending on the presence or absence of somatic hypermutation, where unmutated U-CLL are associated with remarkably worse prognosis than mutated U-CLL. The aim of the study was evaluation of rearrangement of IG genes profile in Macedonian CLL patients in line with facts that there are some geographic linked variations in IG genes. Methods: In this study, mutational status and configuration of IGHV-IGHD-IGHJ rearrangements in 70 treatment naïve CLL patients were analyzed using reverse transcriptase– polymerase chain reaction (RT-PCR) and sequencing methodology at the center for bimolecular pharmaceutical analyses, faculty of pharmacy, Skopje, Macedonia. Results: Our evaluation have shown that 52.8% patients belonged to the U-CLL subset, whereas 47.1% belonged to the M-CLL subset. The most frequently expressed IGHV subgroup was IGHV3 (41.4%), followed by IGHV1 and IGHV4 (28.5%), IGHV5 (1.4%). In the IGHD and IGHJ sets most frequently expressed was IGHD3 (55.7%), IGHJ6 gene (37.1%) respectively. Conclusions: Our evaluation of mutational status on IGVH, IGDH, and IGJH gene in Macedonian CLL patients resulted with data which are consubstantial to those from Mediterranean area and West Balkan
Keywords: CLL; prognosis; mutational status